Multi‐Step Crystallization of Barium Carbonate: Rapid Interconversion of Amorphous and Crystalline Precursors. (15th November 2017) - Whittaker, Michael L.; Smeets, Paul J. M.; Asayesh‐Ardakani, Hasti; Shahbazian‐Yassar, Reza; Joester, Derk
Abstract: The direct observation of amorphous barium carbonate (ABC), which transforms into a previously unknown barium carbonate hydrate (herewith named gortatowskite) within a few hundred milliseconds of formation, is described. In situ X‐ray scattering, cryo‐, and low‐dose electron microscopy were used to capture the transformation of nanoparticulate ABC into gortatowskite crystals, highly anisotropic sheets that are up to 1 μm in width, yet only about 10 nm in thickness. Recrystallization of gortatowskite to witherite starts within 30 seconds. We describe a bulk synthesis and report a first assessment of the composition, vibrational spectra, and structure of gortatowskite. Our findings indicate that transient amorphous and crystalline precursors can play a role in aqueous precipitation pathways that may often be overlooked owing to their extremely short lifetimes and small dimensions. However, such transient precursors may be integral to the formation of more stable phases.